(untitled) (PIONIR: JURNAL PENDIDIKAN, 2025)
Learning media are instruments that help deliver knowledge or messages by using the senses of sight, sound, and touch. Learning resources are crucial for assisting students in picking up new knowledge and abilities. The dearth of educational media in schools often makes it difficult for students to increase their enthusiasm in learning. Analyzing the requirements, viability, and usefulness of creating Picture Story Book (Flipbook) learning materials for the Heroes curriculum for Grade IV at MIS Kaduaja Tana Toraja is the goal of this study. Using the ADDIE development model, this study employs an R&D (Research and Development) methodology. The five phases of the ADDIE development model are as follows: (1) analysis; (2) design; (3) development; (4) implementation; and (5) evaluation. Twenty pupils and a teacher served as the study’s subjects. A picture story book (Flipbook) with presentation-style learning materials about Tana Toraja heroes was created as a result of this study, which was carried out at MIS Kaduaja Tana Toraja. Tests, questionnaires, interviews, and observations were the methods utilized to collect the data, which were subsequently subjected to both qualitative and quantitative analysis. According to the study’s findings, students require a picture book with vibrant illustrations. According to the criteria, the flipbook storybook media satisfies the requirements for validity and has reached a practical level. Picture Story Book (Flipbook) was validated by three experts as validators including language experts 70% (Valid), material experts 86% (valid), and design experts 72.5% (valid). Meanwhile, for the practical results involving 20 students and a fourth grade homeroom teacher as research subjects obtained very positive values with results of 78.3% of students and 90.38% of fourth grade teachers with a very practical level of practicality. Keywords: Picture Story Book, Flipbook, Heroes